Prihodnost pokojninskega sistema v Sloveniji - Rangus, Andraž (Podjetje in delo, 2018)
The future demographic changes and digitalisation present a major challenge for social security systems across Europe. An aging society, societal changes and changes in the labour market due to new technologies will require adjustment of today's social insurance systems, and especially the pension insurance systems. Slovenia, where the aging of the population is even more pronounced, will have to thoroughly consider the functioning of the existing pension insurance scheme in the future in order to ensure its basic mission, i.e. ensuring adequate income for all generations, as well as its long-term sustainability. The debate on the changes of the Slovenian pension system already began in 2016 with the preparation of the White Paper on pensions. The conclusion of this debate is manifested in a document adopted by the Economic and Social Council, with which social partners reached an agreement on key guidelines for future legislative changes in the area of pension and disability insurance. The legislator has thus laid the foundations for adopting a new law that will regulate the field of pension and disability insurance, and adapt this form of social insurance to the new socio-economic conditions.
Keywords: demografija; digitalizacija; pokojninsko in invalidsko zavarovanje; sistemi socialne varnosti; spremembe